Determinants Of Gojek Driver Income In Badung Regency, Bali Province - I Gusti Agung Istri Agung Kemala Widyatmika Muncana Putri; I Nyoman Wahyu Widiana (International Forum of Researchers and Lecturers, 2025)
Gojek, as one of the largest online transportation service providers in Indonesia, has significantly transformed patterns of mobility and created employment opportunities for many individuals. Founded by Nadiem Makarim in 2010, Gojek is the first online-based transportation company originating from Indonesia. This study aims to examine the effects of working hours, number of orders, age, and gender on the income of Gojek drivers in Badung Regency. The research was conducted in Badung Regency, a major tourism hub in Bali Province, which generates high demand for online transportation services. Data were collected using a quantitative approach and an associative design through surveys administered to Gojek drivers in the region. The results of the analysis indicate that these variables collectively influence driver income. Specifically, working hours, number of orders, and gender have a positive and significant effect, while age has a negative and significant effect on income.